Implementation of Occupational Therapy Through Bead Stringing Training to Improve the Independence of ODGJ at Posyandu Jiwa Giwangretno Village Kebumen District - Sulaeman, A.Sulaeman; Witata, Kukuh Pragas; Ma‘waa, Syafa‘ Fannayya; Utami, Langgeng Laksita; Saputri, Fadila; Hidayah, Kurnia Nur; Stefhanie, Nadia; Saputra, Rifai’z Zaki; Laksono, Brayan Tri; Khusnaka, Arini; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Mental health is the condition of a person who is balanced in mental and physical aspects. This study addresses the problem of the prevalence of People with Mental Disorders (ODGJ) in Giwangretno Village, Kebumen Regency, which causes a decrease in the quality of life and independence of the sufferers. The objective was to improve the independence of ODGJ through the application of occupational therapy through bead training at the local Mental Position, which is expected to train their independence and productivity. The method used was a one-day training involving ten ODGJ in the rehabilitation stage, consisting of four sessions: socialization, beadwork training, independent practice, and evaluation, using craft and manicure tools. The results showed that 70% of the ODGJ participants managed to achieve independence in making accessories, although the other 25% still needed assistance, proving the effectiveness of occupational therapy in improving their enthusiasm and quality of life. Impulsively, bead occupational therapy is an effective method to support the healing process and increase independence of ODGJ, and is recommended to be integrated in the Kreasi Warna Jiwa program.